Comparison analysis of imported coffee of Malaysia from Indonesia and Vietnam - Eko Atmadji; Esther Sri Astuti S. A.; Yosra Hersegoviva Suhardiman (Economic Journal of Emerging Markets, 2018)
Malaysia is an important coffee export destination for Indonesia. Recently Vietnam shifts Indonesian position as a number one coffee exporter in Malaysia. Based on this background, this study compares the position of Indonesian and Vietnamese coffee in the eyes of Malaysians by using demand function. The data is time series and co-integration test should be applied. Co-integration test is using Bound Test in ARDL method. Indonesian coffee demand by Malaysians is co-integrated, whereas the demand for Vietnamese coffee by Malaysia does not contain co-integration. It means, Vietnamese coffee is not a serious competitor to Indonesian coffee in Malaysian market.